Evaluation of Improving Water Flooding Technology by Volume Fracturing of Water Injection Wells in Complex Fractured Reservoirs: A Case Study of Chang 6 Reservoirs in Huaqing Oilfield, Ordos Basin - Shengping He; Jiaosheng Zhang; Chao Li; Xiqun Tan; Yi Ping; Desheng Li; Jiang Chen (Geofluids)
Given the problems of multiple natural microfractures developed in Chang 6 reservoir of Huaqing oilfield in Ordos Basin, the injected water flows along with the natural fractures during water injection development, resulting in low water drive recovery. The concept of volume fracturing is introduced into water injection well fracturing, and the technical idea of reconstructing the seepage field through volume fracturing of water injection well is proposed to improve the water flooding effect. On the basis of previous studies, firstly, the development of fractures and the rock mechanical properties of reservoirs are studied, and then the expansion law of volumetric fracturing fractures in the study area is analyzed. Combined with numerical simulation research, the feasibility of improving water drive by volumetric fracturing in water injection wells is demonstrated. Based on the above research, field tests of three well groups are carried out. The test shows that the volume fracturing of water injection wells can form a fracture zone along the direction of the maximum principal stress (with an average bandwidth of 56 meters), and then change the original dominant direction of water drive to realize the effective matching between fractures and injection production well pattern; the row spacing is reduced, and the effect of waterflooding is improved obviously. After the test, the average daily oil production of a single well increased from 0.6 tons to 1.0 tons, the water cut decreased from 74.6% to 42.0%. The oil recovery rate increased from 0.44% to 0.77%. The recovery increased by 5-8%.